2005
DOI: 10.1097/00128488-200504000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Climate in Nursing Practice

Abstract: Clarity in an organization's mission, vision, and values is key to effective management in today's complex healthcare work environment. To clearly articulate mission, vision, and values, employees must experience consistency between what is espoused and what is lived. The purpose of this article is to discuss the nurse leader's role in ensuring congruence between caring missions and caring practices. Ethical principles are discussed as the foundation necessary for creating an ethical climate for nursing practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…The leaders of the organization play a key role in building, maintaining, and encouraging an ethical environment and climate. It is the main responsibility of the leadership in the organization to create and sustain an ethical environment and climate, because these not only stand for what ought to be done but also encourage good practice [15]. Therefore, the leaders should devote all their efforts to fostering an ethical environment and climate in the organization [16].…”
Section: Introductionmentioning
confidence: 99%
“…The leaders of the organization play a key role in building, maintaining, and encouraging an ethical environment and climate. It is the main responsibility of the leadership in the organization to create and sustain an ethical environment and climate, because these not only stand for what ought to be done but also encourage good practice [15]. Therefore, the leaders should devote all their efforts to fostering an ethical environment and climate in the organization [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although the impact of organisational ethical climate has been demonstrated in the business literature to infl uence behaviour and decision making of participants within that environment, it is underdeveloped in the nursing literature. Ethical climate is increasingly being linked to negative outcomes such as reduced job satisfaction and turnover (Hart, 2005;Shirey, 2005;Ulrich et al, 2007), however the impact of nurses' workplaces on nurses' understanding of responsibility, behaviour and decision making remains unsubstantiated. Some authors have suggested that nurses are working 'in between' the values of the organisation and their own values (Varcoe et al, 2004) but more understanding of how nurses successfully negotiate this is imperative since nurses are central to the delivery of care.…”
Section: Limitations Of the Reviewmentioning
confidence: 99%
“…When managers make decisions, they must respect the stakeholders' right, think over different influence of decisions on stakeholders, and weigh profit distribution between enterprises and stakeholders. Decisions still remain on integrity level and couldn't reach fair level if managers couldn't completely meet with abovementioned requirements (Shirey, 2005). Otherwise, decisions could realize fair and justice, which is great ethical improvement to the enterprise.…”
Section: Fair Levelmentioning
confidence: 99%